Analysis of the Effectiveness and Impact of Cash Social Assistance of the Covid-19 Pandemic on Consumption Expenditures of Poor Households (Muslim Majority) in Indonesia - Dinda Pramisita, Anak Agung; Nyoman Saskara, Ida Ayu; Marhaeni, Anak Agung Istri Ngurah; Wiwin Setyari, Ni Putu (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The purpose of this study was to analyze the effectiveness of the cash social assistance program during the COVID-19 Pandemic and to analyze the impact of cash social assistance on poor households (Muslim majority). This research was conducted on people who received social assistance of muslim majority in Muslim minority areas Badung Regency, Bali from May 2021 to February 2022. The sample for this study was 99 families receiving social assistance and 103 families who did not receive social assistance, so that the total sample is 202 families. Samples of the treatment group in this study are non-probability sampling and saturated samples for the control group. The data analysis technique used qualitative effectiveness analysis and public policy impact evaluation analysis. Based on the results that the effectiveness of the cash social assistance program is very effective. Social assistance increases food expenditure for households receiving social assistance compared to non-recipient assistance. Social assistance has a significant influence on household spending, especially for food in the Muslim community.